2003
DOI: 10.2337/diabetes.52.5.1182
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adiponectin Levels Are Reduced in Nonobese but Insulin-Resistant First-Degree Relatives of Type 2 Diabetic Patients

Abstract: Adiponectin, one of the most abundant gene transcript proteins in human fat cells, has been shown to improve insulin action and is also suggested to exert antiatherogenic effects. We measured circulating adiponectin levels and risk factors for atherosclerosis in 45 healthy first-degree relatives of type 2 diabetic subjects (FDR) as well as 40 healthy control subjects (CON) without a known family history of diabetes. Insulin sensitivity (S i ) was studied with the minimal model, and measurements of adiponectin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
95
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 42 publications
13
95
1
Order By: Relevance
“…On the other hand, there were strong consistent associations between adiponectin and plasma lipids, particularly plasma triglycerides (negative), HDL-C, Apo A1 and NEFA (positive). This strong association of adiponectin with HDL metabolism has been previously noted [40][41][42][43][44][45][46][47] and in fact in a study with 4500 subjects, it was proposed as a useful marker/risk factor in cardiovascular disease assessment. 40 While the physiological nature of this correlation has not been determined, this may be tied to the proposed functions of adiponectin at the vascular wall which include modulation of endothelial function, inhibition of vascular smooth muscle proliferation, suppression of macrophage transformation and modulation of inflammation (for a review, see Ukkola and Santaniem 22 ).…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, there were strong consistent associations between adiponectin and plasma lipids, particularly plasma triglycerides (negative), HDL-C, Apo A1 and NEFA (positive). This strong association of adiponectin with HDL metabolism has been previously noted [40][41][42][43][44][45][46][47] and in fact in a study with 4500 subjects, it was proposed as a useful marker/risk factor in cardiovascular disease assessment. 40 While the physiological nature of this correlation has not been determined, this may be tied to the proposed functions of adiponectin at the vascular wall which include modulation of endothelial function, inhibition of vascular smooth muscle proliferation, suppression of macrophage transformation and modulation of inflammation (for a review, see Ukkola and Santaniem 22 ).…”
Section: Discussionsupporting
confidence: 59%
“…Our study demonstrates that FHD is associated with hypoadiponectinemia that supports findings of previous studies (9,10). In a recent study, in 64-year-old women in Sweden, mean ADIPOQ levels were lower (11.4 vs 13.9) in those with FHD than those without FHD (10).…”
Section: Discussionsupporting
confidence: 79%
“…In a recent study, in 64-year-old women in Sweden, mean ADIPOQ levels were lower (11.4 vs 13.9) in those with FHD than those without FHD (10). In another study in male subjects in Sweden, firstdegree relatives of type 2 diabetic patients also had significantly lower ADIPOQ levels (9). The present study showed an inverse relationship between FHD and ADIPOQ levels in Korean men and women.…”
Section: Discussionmentioning
confidence: 52%
“…Further differences in the action of both peptides have also been reported. In contract to resistin, adiponectin levels correlated negatively with obesity [46], dyslipidemia [47], coronary artery disease [48], insulin resistance [49], [50] and inflammation. Since hypertrophy is one of the earliest manifestations of cardiac dysfunction, such effects further support a role of adipokines in the development of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%